Iron determination in multivitamin tablets: Enhancing military nutritional preparedness based linear regression method - Agus Eko Prasojo; Reza Anitasari; Windy Nelasari Sijabat; Naufan Nurrosyid (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2023)
AAS is also an important method that has the most extensive application in metal analysis. most of the determinations were carried out by thin spectrophotometry, therefore an experiment was carried out to determine the Fe content in multivitamin tablets using the atomic absorption spectrophotometry method has high selectivity and sensitivity. Standard solution preparation. Prepare a standard solution of Fe with a concentration of 1, 2, 3, 4, and 5 ppm, then read the absorbance of the standard solution on AAS. Sample solution preparation and absorbance measurement. Several tablets were put into a beaker and 7 ml of concentrated HCl was added working principle of atomic absorption spectrophotometry is based on the evaporation of the sample solution which will initially be nebulized to form a spray, then it will be desolvated to form a dry aerosol until it is evaporated and converted into free atoms.. Iron levels in samples using AAS can be found by measuring the intensity of the radiation that decreases after being transmitted. The reduction in radiation intensity is proportional to the concentration of the sample element in the sample being measured. By testing the t-test, it was found that the AAS instrument was more sensitive to low concentrations